Rare bilateral presentation of morning glory disc anomaly - Dedhia, Chintan Jethalal (BMJ Case Rep, 2016)
A 4-year-old girl presented with a history of poor vision and oscillation of both eyes since infancy. Ocular examination revealed the best corrected visual acuity of 2/60 in right eye and 3/60 in left eye. Horizontal pendular nystagmus was present in both eyes. Fundus examination revealed morning glory disc anomaly (MGDA) bilaterally. Radiographic imaging of the brain revealed central nervous system anomalies. The guarded visual prognosis was explained and the patient referred for low vision rehabilitation and advised yearly follow-up. MGDA is very rarely bilateral. We aim to highlight the distinguishing features of bilateral MGDA from other excavated optic nerve head anomalies which could also present bilaterally but vary in their associations, management and prognosis.